Proceedings of the 2013 IEEE/ACM International Conference on Advances in Social Networks Analysis and Mining 2013
DOI: 10.1145/2492517.2500307
|View full text |Cite
|
Sign up to set email alerts
|

Mining tourist routes using Flickr traces

Abstract: This paper is about a new methodology to automatically rebuild main paths from Flickr's traces. Our geotagged image metadata's corpus allows the construction of each photographer's timeline. The tourist's itinerary in the destination can then be reconstructed considering two modes: the fastest path and the most likely path. Major paths are directly extracted from the fusion of all itineraries. To illustrate the multi-scale efficiency of this work, several fields of study are presented : Berlin, the Loire Valle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 5 publications
(3 reference statements)
0
6
0
Order By: Relevance
“…In group 2, when the information is collected after the visit, the option D "Patterns of tourist mobility, based on geolocalized photographs" is mainly developed in References [128,149,157,230,240,243,266]. These studies are based on the database of tagged photographs available on social networks.…”
Section: Discussionmentioning
confidence: 99%
“…In group 2, when the information is collected after the visit, the option D "Patterns of tourist mobility, based on geolocalized photographs" is mainly developed in References [128,149,157,230,240,243,266]. These studies are based on the database of tagged photographs available on social networks.…”
Section: Discussionmentioning
confidence: 99%
“…Social media sources (photo sharing web sites such as Flickr, Twitter, Panoramio or Instagram; or social sport tracker sites and applications such as Wikiloc or Strava) connected with tourism activity, have contributed greatly to ameliorating both data collection and analysis issues, potentially contributing to urban tourist research. As stated by Chareyron et al [55], big data unquestionably represents a new challenge for tourism. In addition, the recent widespread use of camera devices with GPS (including smartphones and tablets) enables storing geographical information for each photo taken.…”
Section: Geotagged Social Media Sourcesmentioning
confidence: 99%
“…In the field of tourism, geotagged photos published on social network sites are surely the more exploited objet for studying people' activities and behaviour related to touristic places [8]. More particularly, considering the case of cultural routes, Chayeron et al [9] showed that the analysis of digital traces retrieved on the photo-sharing platform Flickr can help to rebuild the spatial path of a given tourist and to identify the most popular tourist points.…”
Section: State-of-the-artmentioning
confidence: 99%
“…This can be the case, for instance, of accounts that have a similar goal such as two cyclists' clubs. Or, this can be the case of websites financed by advertising, such as eventi_della_tuscia 9 which revenues is subject to its audience (in terms number of visitors, numbers of clicks on advertising).…”
Section: Figure 4 Intra-and Inter-class Linksmentioning
confidence: 99%